2020
DOI: 10.1007/s41748-020-00191-5
|View full text |Cite
|
Sign up to set email alerts
|

Vicia sativa Roth. Can Reduce Soil and Water Losses in Recently Planted Vineyards (Vitis vinifera L.)

Abstract: Elevated soil loss and runoff rates can reduce soil fertility; therefore, soil erosion control strategies must be implemented at the hillslope and watershed scale when plantations are established and the soil is bare. In this research, we propose the use of the Vicia sativa Roth. to reduce the soil losses during the first year to control the peak of soil erosion after the plantation in tilled vineyards. To test its efficiency, rainfall simulation experiments were carried out with field surveys in The Casa Pago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 112 publications
(99 reference statements)
1
34
0
1
Order By: Relevance
“…Ulmer et al [114] also reported that residue removal did not affect corn, soybean, and bean yields. These successful results can be compared to other strategies applied in recent research, such as the use of cover crops, where water availability and crop production were higher than leaving the soil bare [115,116].…”
Section: Wheat and Corn Yieldmentioning
confidence: 87%
“…Ulmer et al [114] also reported that residue removal did not affect corn, soybean, and bean yields. These successful results can be compared to other strategies applied in recent research, such as the use of cover crops, where water availability and crop production were higher than leaving the soil bare [115,116].…”
Section: Wheat and Corn Yieldmentioning
confidence: 87%
“…Consequently, this leads to a loss of soil fertility, soil quality, and loss of ecosystem services [120]. It should be noted, however, that extensive soil loss is not limited to vineyards; different authors have reported similar problems in various other crops [121][122][123][124]. Research has suggested that soil loss in vineyards is above the level that amounts to tolerable soil loss, less so for older vineyards with more organic matter content and higher bulk density in relation to younger vineyards [125] Moreover, accurately measuring soil loss in vineyards is fraught with difficulties, because different methodologies available tend to give different results.…”
Section: (Un)sustainable Agronomic Management and Resulting Soil Lossmentioning
confidence: 99%
“…However, this optimal design requires further verification in field because nutrient loss was studied at a plot scale in our experiment. Importantly, to improve rainwater collection and soil conservation, modifications have been applied in contour ridge system, such as double furrows with raised beds [ 56 ], plastic film mulching [ 57 ], the use of catch crops [ 58 ], tied ridge [ 59 ]. Moreover, changes to the drainage layout have been considered to reduce seepage occurrence to further control nutrient loss, such as leading the water flow to converge in the form of a “V”, or to shunt in an inverted “V” [ 60 ].…”
Section: Discussionmentioning
confidence: 99%